Metodologia de ensino jigsaw em disciplina de química medicinal - Massi, Luciana; Cerrutti, Bianca Machado; Queiroz, Salete Linhares (Sociedade Brasileira de Química, 2013)
In this paper, we describe an educational experience involving the use of the jigsaw method on the Medicinal Chemistry course at the University of São Paulo, Brazil. The goal of this proposal was to investigate acceptance and contributions of the method to undergraduate chemistry teaching. Feedback on the jigsaw method collected from the focus groups and questionnaires showed that participants generally acknowledged the advantages of the jigsaw method in helping them learn the Medicinal Chemistry subject. Suggestions for improving the jigsaw method were also received from participants.
The jigsaw method on a medicinal chemistry course
Keywords: Medicinal Chemistry; didactic tool; higher education